Mapas coropléticos e isopléticos y cartografía de potenciales de población - Calvo Palacios, José Luis; Pueyo Campos, Ángel (Geographicalia, 2017)
This paper studies some of the possibilities offered to us by the use of population potentials in relation with traditional cartographies of densities and population representations. It shows the differences between density maps of population potentials developped by administrative unities and representations of isolines and counting cells.